Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ejhg.2012.195
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the spectrum of TUBA1A-related cortical dysgenesis to Polymicrogyria

Abstract: De novo mutations in the TUBA1A gene are responsible for a wide spectrum of neuronal migration disorders, ranging from lissencephaly to perisylvian pachygyria. Recently, one family with polymicrogyria (PMG) and mutation in TUBA1A was reported. Hence, the purpose of our study was to determine the frequency of TUBA1A mutations in patients with PMG and better define clinical and imaging characteristics for TUBA1A-related PMG. We collected 95 sporadic patients with non-syndromic bilateral PMG, including 54 with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 30 publications
0
52
0
1
Order By: Relevance
“…5,10 Mutations in the TUBA1A gene have been associated with various grades of lissencephaly, ranging from the complete loss of gyri and sulci (agyria) to simplified abnormally thick convolutions (pachygyria), and perisylvian polymicrogyria (PMG). [11][12][13][14][15][16][17][18][19] Mutations in the TUBB2B gene have been associated with bilateral, asymmetrical PMG 20 and schizencephaly 21 as well as symmetrical PMG and pachygyria. 22,23 Axon guidance disorders (corpus callosum abnormalities and hypoplasia of the oculomotor nerves) and cortical malformations (PMG and gyral disorganization) have been found in individuals carrying defects in the TUBB3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Mutations in the TUBA1A gene have been associated with various grades of lissencephaly, ranging from the complete loss of gyri and sulci (agyria) to simplified abnormally thick convolutions (pachygyria), and perisylvian polymicrogyria (PMG). [11][12][13][14][15][16][17][18][19] Mutations in the TUBB2B gene have been associated with bilateral, asymmetrical PMG 20 and schizencephaly 21 as well as symmetrical PMG and pachygyria. 22,23 Axon guidance disorders (corpus callosum abnormalities and hypoplasia of the oculomotor nerves) and cortical malformations (PMG and gyral disorganization) have been found in individuals carrying defects in the TUBB3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work, however, has shown that all of the six grades of classic lissencephalies (Table 1) are caused by mutations of genes encoding tubulins ( primarily TUBA1A) (Poirier et al 2007) or proteins that function in conjunction with microtubules (microtubule-associated proteins or MAPs, such as DCX, LIS1, cytoplasmic dynein, kinesins, NudE) (Dobyns et al 1993;Gleeson et al 1998;Toyo-oka et al 2003;Lecourtois et al 2010;Cushion et al 2013;Poirier et al 2013). As mutations of genes encoding tubulins and MAPs are associated with, and likely responsible for, other MCDs (such as heterotopia and polymicrogyria [PMG]-like cortex) (Poirier et al , 2012Guerrini et al 2012;Cushion et al 2013), one might consider altering the classification to make malformations secondary to mutations of tubulin and MAP genes as a major category of MCD with classic lissencephalies as a subcategory. It will be interesting to determine what differences are seen in the mutations of genes coding for MAPs as compared with those coding for the tubulins themselves.…”
Section: Malformations Secondary To Tubulin and Microtubule-associatementioning
confidence: 99%
“…This cyclic process is essential because mice lacking TTL are perinatal lethal (16). Furthermore, mutations in ␣-tubulin residues that are engaged in the tubulin-TTL interface are linked to neurodevelopmental disorders (17,18). Tyrosinated ␣-tubulin dimers are incorporated in polymerizing microtubules, therefore often marking the dynamic plus end of microtubules, which are decorated by microtubule plus end tracking proteins (ϩTIPs) (10,11,19).…”
mentioning
confidence: 99%